MT/D, or change: An anti-racist musical theatre reading group. Issue 1 (1st April 2022) - Galella, Donatella; Asare, Masi; Ealey, Jordan; SAJ,; Kim, Hye Won; Morrison, Matthew D.; Moten, Fred; Shimakawa, Karen; Shimizu, Celine Parreñas
In this roundtable held at the Association for Theatre in Higher Education conference in 2021, the participants discussed the racialized politics of citation in musical theatre studies. Some of the speakers lifted up anti-racist scholarly pieces that have significantly shaped their work: SAJ considered Douglas Jones Jr's chapter 'Slavery, performance, and the design of African American theatre', Jordan Ealey shared lessons from Matthew D. Morrison's article 'The sound(s) of subjection: Constructing American popular music and racial identity through Blacksound', Masi Asare expanded upon Fred Moten's essay 'Taste, dissonance, flavor, escape' to think through sweeping away and stealing away, Donatella Galella applied Karen Shimakawa's book National Abjection: The Asian American Body Onstage to contemporary yellowface, and Hye Won Kim talked about the influence of Celine Parreñas Shimizu's book The Hypersexuality of Race: Performing Asian/American Women on Screen and Scene on her own work. Morrison, Moten, Shimakawa and Shimizu reflected on why they wrote those pieces of scholarship and how they understand their research years later. Finally, the co-authors spoke to reasons why scholars situated in musical theatre studies have so rarely cited research in fields like Black and Asian American performance studies and imagined radical possibilities beyond a racist citation framework.